EFEKTIVITAS PELATIHAN TEAM WORK BUILDING MELALUI OUT DOOR ACTIVITIES DALAM MENINGKATKAN KAPITAL SOSIAL = THE EFFECTIVITY TEAMWORK BUILDING TRAINING BY OUT DOOR ACTIVITIES ON SOCIAL CAPITAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The aim of this research was to examine the effectively of teamwork building training by out-door activities on social capital score's subject. Many approaches have indicated that cohesive group or teamwork has a positive impact on human productivity. Therefore, the hypothesis is teamwork building training by out-door activities makes good teamwork that give contribution to social capital ". Fourty subjects participated in this study. Subjects were divided into two groups, 20 subjects were experimental group and 20 subjects were control group. This design research was pretest-posttest experimental and control groups. The result of this research shows that teamwork building training by out-door activities has a positive impact on social capital (t, = 2,853 p < 0,05) and contribution to increase social capital 53,9%. In conclusion, teamwork building training by out door activities has a positive and steady affect on social capital. Keywords: Social capital, team work building, out door activies